The Antigenotoxicity of Eruca sativa Mill Extract on Bone marrow Cells of Male Albino Mice Treated With Vincristine - Mahdy, S.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Chemotherapy drugs have a major role in fighting cancer but, that doesnâ€™t mean they are clear from side effect on human health. One of these drugs is vincristine this study, the chemopreventive potency of the crude extract ofIn Eruca Sativa Mill Which have a good reputation as antioxidant and anticancer against chromosomal aberration and suppressed mitotic index in bonemarrow cells of male albino mice treated with 50Âµ1 of vincristine intrapritoneally(ip) have been detected. Results Showed a Significant increasing in the percentage of the mitotic index nearly to the control group and a significant decrease in chromosomal aberration after (35) days of treatment with 250 mg/kg crude extract of Erucasativa. These results suggested a strong antigenotoxicity effect against vincristine damages onbonemarrow cells.